Nonlinear price transmission and asynchronous price bubbles: Empirical evidence from China's agricultural futures and spot markets - Qianqian Mao; Yanjun Ren; Jens-Peter Loy (Journal of Applied Economics, 2024)
Previous studies on commodity price bubbles mainly focused on futures markets and ignored the performance of spot markets. Using the price data for corn and soybeans in China, this study identifies the exact bubble dates for the futures and spot markets, and finds asynchronous price bubbles between these two markets. Bubbles are more frequent for commodity spot prices, while the corresponding futures prices still dominate the process of price discovery. Further analysis reveals that, the lack of (immediate) linear transmission between the cointegrated prices may have inhibited bubble synchronization, and caused more spot price bubbles. The nonlinear transmission effects between the futures and spot prices suggest the existence of speculative storage and market power. This may further explain why spot price bubbles cannot be arbitraged away.
Keywords: 330; agricultural commodities; futures market; Price bubbles; spot market